PENGARUH KELENGKAPAN PERSYARATAN ADMISI PASIEN BPJS TERHADAP EFEKTIVITAS PELAYANAN DI RSUD KABUPATEN SUMEDANGPENGARUH KELENGKAPAN PERSYARATAN ADMISI PASIEN BPJS TERHADAP EFEKTIVITAS PELAYANAN DI RSUD KABUPATEN SUMEDANG - Ceria Febiana; Yaya Suparya (POLITEKNIK PIKSI GANESHA, 2021)
This study aimed to determine the effect of completeness of admission requirement for BPJS (Social Insurance Administration Organization) for inpatients on to effectiveness of admission services in Sumedang General Hospital. Data collection method is by distributing questionnaires and interview which is equipped with literature review that have close relevance to the subject matter. The result showed Spearman rank correlation coefficient value 0.97 is in the interval from 0.8 to 1.000 which is categorized as very strong and it is known that the completeness of admission requirements for BPJS patients hospitalized affects the effectiveness of admission services by 94, 09%. As for the obstacles in completing BPJS patient admission requirements are, (1) NIK (Population Registration Number) BPJS is not in accordance with the NIK contained in the KTP / Family Card, (2) Patients with delinquent payments / late from the 10th to pay BPJS health insurance and (3) No BPJS center facilities in Sumedang General Hospital. The advice given are that the (1) Family / patient should not ignore the NIK contained on the BPJS card when they making the BPJS health insurance, (2) Family / patient must consider about the payment of BPJS insurance payment ant make it as priority, the payment not later than 10th in every month and (3) Sumedang General Hospital should have special facilities or rooms for BPJS centers, so that everything that is problematic with the health BPJS card will be quickly handled